FOLLOWERS' PERCEPTIONS OF SPORTS CONTENT ON @ANDREADIANBIMO'S INSTAGRAM ACCOUNT - Novira, Yestia; Widiasanty, Gita (Transpublika Publisher, 2024)
This study aims to find out how followers of the @andreadianbimo Instagram account perceive the sports content they upload. The research method used is descriptive qualitative method which aims to explain certain events clearly and in detail. Data collection technique used is interview. There are 5 informants who are followers of the Instagram account @andreadianbimo. The results of this study found 3 main categories which became the subject of the answers from the five informants interviewed. First, the Instagram account @andreadiabimo motivates its followers to start exercising and living a healthy life. Second, @andreadianbimo's informative sports content so that his Instagram followers can get information about sports through his account. Third, sports content on the Instagram account @andreadianbimo is interesting so that informants keep following the @andreadianbimo account. The findings suggest that @andreadianbimo's Instagram account plays a pivotal role in motivating followers to adopt healthier lifestyles, providing valuable sports-related information, and maintaining follower engagement. These insights underscore the importance of influential social media figures in promoting health awareness and fostering community engagement among their followers.